The Role of Foreign Policy in International Student Mobility: The Case of the Turkish “Opening to Africa” Policy - Mehmet Köse; Hacer Atabaş (Üniversite Araştırmaları Dergisi)
This article examines the impact of foreign policy decisions, specifically the Africa Opening Policies, on international scholarship programs and student mobility from Africa to Türkiye. The background of Türkiye’s African policy is discussed, along with policies made by different governments. The article evaluates student exchanges and scholarships in bilateral agreements and regional cooperation between Türkiye and African countries. The central question is whether the openings in Turkey's African policy have had any effect on student mobility from Africa. To answer this question, the article uses international scholarship programs as an instrument in Turkish foreign policy in the context of the Africa Opening Policies as a single case study, which is designed to provide an in-depth understanding and contextualization of scholarship programs within foreign policymaking. Analyzing the policy documents from relevant institutions such as the Council of Higher Education, the Ministry of National Education, and the Presidency of Turks Abroad and Related Communities, the study uses process tracing methodology to show that foreign policy openings and desired relations with a particular country or region affect the design and priorities of international higher education programs. Thus, the article explores foreign policymaking as a driving factor in developing international student mobility in Türkiye.